Digital time with parents in initial education: improving digital skills - Cortijo Osores, Geraldine del Carmen (2023)
There are many studies of digital technology in teachers and students, however, in parents the previous literature is scarce, possibly because the importance of information technologies in this population had not been considered, even more so in circumstances in which They became co-protagonists of the educational processes in virtuality. The study aimed to apply workshops to improve basic digital skills in initial education. It proceeds with the pre-experimental design (pre- and post-test) for a sample of 42 participants selected by intentional non-probabilistic sampling and as a relevant result, the majority of the participating subjects raised the initial averages by 11 points, findings verified after the application of the program. From the study it is concluded that a determining cause of the announced weaknesses is due to the fact that the participating subjects do not correspond to the technological generation, constituting a challenge faced by teachers, parents and children. Finally, it was possible to determine that the program contributes to the performance of the companions in remote education and therefore improves the learning of boys and girls in order to strengthen pedagogical processes mediated by digital technology.